Sexual Orientation Wage Gaps across Local Labour Market Contexts: Evidence from Canada - Denier, Nicole; Waite, Sean (Relations industrielles / Industrial Relations, 2017)
SummaryMounting evidence suggests that sexual orientation matters in the labour market. Research in Canada points to a wage hierarchy not only by gender, but also by sexual orientation, with heterosexual men out-earning gay men, lesbians, and heterosexual women. While previous work has considered how human capital characteristics, occupation and industry of employment, and family status factor into the creation of these earnings disparities, little research has examined how residential concentration in large metropolitan areas factors into the creation of sexual orientation pay gaps.Drawing on the 2006 Census of Canada, this study investigates how sexual orientation wage gaps vary across geographic areas in Canada, documenting earnings disparities across the metropolitan/non-metropolitan divide as well as for Toronto, Montreal and Vancouver. We also evaluate whether the mechanisms contributing to wage gaps diverge across these contexts, focusing on how pay gaps differ across occupations, points in the earnings distribution, and sectors of employment.Our results show that pay gaps are highest in non-metropolitan Canada. The underlying components of wage gaps fluctuate across Canada, especially for gay men. Sexual orientation earnings penalties are reduced in public sector employment, even where private sector wage gaps are highest. These results suggest that local social and labour market contexts are associated with the earnings outcomes of sexual minorities.